Progressivity of Burden-Sharing in a Lindahl Equilibrium - Wolfgang Buchholz; Dirk Rübbelke (Center for Economic Studies and ifo Institute (CESifo), 2017)
In this paper, we show that progressivity (regressivity) of burden sharing in a Lindahl equilibrium is a direct consequence of gross complementarity (substitutability) between the private and the public good when the public good is taken as the numéraire. We, moreover, link the respective conditions for gross complementarity to the more familiar ones in which the private good serves as the numéraire.
Keywords: D63; H23; H41; 330; Lindahl equilibrium; progressive (regressive) burden sharing; complements and substitutes